2016
DOI: 10.4236/ns.2016.811047
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Sex Inversion of Chicken Embryos at Aromatase Inhibition, Estrogen Receptor Modulation, DNA Demethylation and Progesterone Treatment

Abstract: The work was carried out by microinjections of an aromatase inhibitor letrozole, an estrogen receptor modulator tamoxifen in incubated eggs Gallus g. domesticus, the first day of incubation. It also used 5-azacytidine (5-AC) at the same time. Injection of progesterone was carried out before the onset of meiosis prophase 1 on 16 h of incubation. Morphologically and histologically and by PCR, sex of the 17-day embryos was controlled. According to information received microinjection of letrozole caused almost a 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…• Studies with chicken (Gallus g. domesticus) embryos with the aromatase inhibitor letrozole on the first day of embryonic development has shown that the gonad of genetic females had poorly developed seminiferous tubules suggesting that they had undergone testicular sexual differentiation (Trukhina et al 2016).…”
Section: Birdsmentioning
confidence: 99%
“…• Studies with chicken (Gallus g. domesticus) embryos with the aromatase inhibitor letrozole on the first day of embryonic development has shown that the gonad of genetic females had poorly developed seminiferous tubules suggesting that they had undergone testicular sexual differentiation (Trukhina et al 2016).…”
Section: Birdsmentioning
confidence: 99%